SEL1L–HRD1 ERAD–autophagy interplay maintains mitochondrial homeostasis in brown adipocytes - Xinxin Chen; Siwen Wang; Mauricio Torres; Sijie Hao; Shengyi Sun; Ling Qi (Proceedings of the National Academy of Sciences, 2026)
Mitochondrial integrity is central to energy homeostasis, particularly in brown adipose tissue where dynamic remodeling fuels thermogenesis. Two major proteostatic systems, the SEL1L–HRD1 endoplasmic reticulum (ER)-associated degradation (ERAD) pathway and autophagy, have been shown to intersect in vitro, but their physiological coordination in metabolically active tissues remains unclear. Here, we demonstrate that ERAD and autophagy act in synergy to safeguard mitochondrial integrity in brown adipocytes. Using various adipocyte-specific knockout (KO) mouse models and high-resolution ultrastructural 2D and 3D imaging, we show that simultaneous deletion of Sel1L and Atg7 (double KO, DKO) causes striking mitochondrial abnormalities under room temperature, absent in single KO or Sel1L-Ire1a double knockout mice. DKO adipocytes accumulate hyperfused megamitochondria extensively penetrated by ER tubules, accompanied by ER expansion, excessive ER–mitochondrial contacts, and impaired thermogenesis. These findings reveal that SEL1L–HRD1 ERAD and autophagy cooperate, rather than act redundantly, to maintain mitochondrial integrity in brown fat, uncovering a previously unrecognized mitochondrial surveillance mechanism based on ERAD–autophagy crosstalk.